2021
DOI: 10.18549/pharmpract.2021.1.2251
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacists’ use, perception and knowledge on dietary supplements: a cross sectional study

Abstract: Background: Pharmacists are commonly tasked with recommending the appropriate dietary supplement and advising the patients of their correct and safe use. Previous research, conducted on pharmacy students, showed that they did not always use the evidence based sources of information, with personal use identified as a significant predictor influencing the decision to recommend a supplement. Objectives: To compare use, perceptions and knowledge of dietary supplements of pharmacists with different years of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
(29 reference statements)
4
6
0
Order By: Relevance
“…Small differences in knowledge levels were found in relation to gender and pharmacy role, while no difference was found in relation to type of degree. These results partially confirm those previously reported by Bukic et al, with the exception of work experience which in their case made no difference in knowledge level ( Bukic et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Small differences in knowledge levels were found in relation to gender and pharmacy role, while no difference was found in relation to type of degree. These results partially confirm those previously reported by Bukic et al, with the exception of work experience which in their case made no difference in knowledge level ( Bukic et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…In general, this study has shown that pharmacists’ knowledge of dietary supplements is low, with only one third of pharmacists above the level considered the minimum standard. These results seem to confirm what was already found in a review on this topic, where the median knowledge score was 64 % ( Waddington et al, 2015 ), but contrast with the high level of knowledge recently reported by Croatian colleagues ( Bukic et al, 2021 ). The main knowledge gaps were related to the RDA for vitamin K, the increasing evidence for the carcinogenic role of multivitamin misuse, and the possibility that multivitamins contain unlabeled toxic ingredients.…”
Section: Discussionsupporting
confidence: 90%
“…Registration of CAM products with the national regulatory body (NAFDAC) will improve acceptance and in addition alignment of the CAM used with cultural and religious beliefs will increase the prevalence of CAM use. This corroborates findings on predictions of the future use of CAM 14 . Over one-third of health professionals will advise others to seek CAM for COVID-19 as is the case 13 .…”
Section: Discussionsupporting
confidence: 90%
“…Still, clinicians have divided opinions because most consider nutraceuticals relatively safe for consumption, but they recognize the need to undergo documented clinical trials such as pharmaceuticals [ 101 ]. However, many health professionals recommend using nutraceuticals influenced by their personal use or work experience and not by high-quality information sources [ 102 ]. The use of nutraceuticals for health and disease remains controversial and limited by the gap between clinical evidence and users’ knowledge.…”
Section: Nutraceuticals Alternative or Complementary Therapy?mentioning
confidence: 99%